EFFECTIVENESS OF IMPLEMENTING SANCTIONS IN THE FORM OF RETURN TO PARENTS AND SUPERVISION OF CHILDREN PERPETRATOR OF THE CRIME OF THEFT - Efendi, Taufik (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
According to Article 82 paragraph (1) letter a of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, it is explained that sanctions that can be imposed on children include returning them to their parents/guardians. In the Banda Aceh District Court from 2015 to August 2016 there were 12 cases in which the perpetrators were children, but only 6 cases resulted in a decision to return the action to the parents. The purpose of writing this article is to explain the judge's considerations in imposing sanctions for returning parents, indicators of the effectiveness of implementing sanctions for returning parents to children who commit criminal acts and to explain the monitoring mechanism for the implementation of sanctions for returning parents. that the judge's considerations in imposing sanctions for returning parents are based on the severity of the crime committed and whether the person concerned has ever committed a crime or not. Applying the sanction of returning parents to children who commit criminal acts is considered better than imposing other sanctions, because children will receive direct supervision and education from their parents, and children will also avoid being labeled and/or branded as perpetrators of criminal acts by society. The monitoring mechanism for the implementation of sanctions for returning to parents is carried out by the Correctional Center (Bapas) for 3 (three) months and the results of supervision from the Bapas regarding children who are returned to their parents are that the child has good behavior such as taking part in community activities where he lives, such as attending recitations and carrying out social activities such as mutual cooperation.